The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4304/jnw.10.9.512-520
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Flow-based Anomaly Detection in Sampled Traffic

Abstract: In recent years, flow-based anomaly detection has attracted considerable attention from many researchers and some methods have been proposed to improve its accuracy. However, only a few studies have considered anomaly detection with sampled flow traffic, which is widely used for the management of high-speed networks. This gap is addressed in this study. First, we optimize an artificial neural network (ANN)-based classifier to detect anomalies in flow traffic. The results show that although it has a high degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Anomaly detection is a broad area of research that has applications in medicine [6], finance [7], computer networks [8,9], and most recently the Internet of things [10][11][12] as well as several other business domains. According to a seminal work by Chandola et al [13], "anomalies are patterns in data that do not conform to a well-defined notion of normal behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anomaly detection is a broad area of research that has applications in medicine [6], finance [7], computer networks [8,9], and most recently the Internet of things [10][11][12] as well as several other business domains. According to a seminal work by Chandola et al [13], "anomalies are patterns in data that do not conform to a well-defined notion of normal behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The adaptive sampling method focuses more on the flows with rare features to improve anomaly detection in sampled traffic. Another two-stage flow sampling technique is proposed in [43] in which a GSA-based classifier is investigated in detecting anomalies in sampled traffic. Then, a flow sampling method is proposed to improve the detection rate.…”
Section: Related Workmentioning
confidence: 99%
“…The accuracy of the proposed MABIDS is calculated for both KDD Cup and CAIDA data sets, and the results are shown in Figure . From this evaluation, it is observed that the results of MAVIDS with CAIDA data set provides higher accuracy when compared with MABIDS with KDD Cup data set.…”
Section: Performance Analysismentioning
confidence: 99%